The Rhythm of the Deal: Negotiation as a Dance - Erik H. Schlie; Mark A. Young (European School of Management and Technology (ESMT), 2008)
In all the literature on the theory and practice of negotiation, the governing metaphor remains consistently one of war or fighting. This is true not only for tactical schools of power-based negotiation, but even for more constructive, interest-based approaches. Our language is infused with talk of tactics, flanks, concessions, gaining ground and winning. This article explores the possible consequences of abandoning this picture in favor of the far too little explored metaphor of the dance. We will see that both the content and the process of negotiation can change dramatically once when we think of bargaining as an aesthetic activity which provides intrinsic joy as well as extrinsic benefits. In such a dance, there is plenty of room for competition as well as cooperation, as movements can be spirited and confrontational as well as smooth and harmonious. We identify many forms of dance in negotiation, and explore three: the dance of positioning, where passions and presentations interact proudly; the dance of empathy, when the partners come to better understand each other; and then the dance of concessions, where the deal is struck and the music comes to an end. Finally, we will try to show how the dance can be employed pedagogically, in teaching and training negotiation and mediation. In particular, the Brazilian dance of capoeira illustrates holistically and experientially how movement and rhythm can be interpreted both as fight and as a dance and how we can come to see a process as both aesthetic and purposeful at the same time. First feeling, then thinking and finally speaking, we can use this medium to explore the dynamics of confrontation and cooperation in a negotiation setting.
urn:nbn:de:101:1-201106143468
Keywords: E32; R10; 650; Negotiation; dance; concessions; bargaining